PENGARUH MEDIA KOLASE TERHADAP KEMAMPUAN PEMANFAATAN LIMBAH PADA MATA PELAJARAN SENI BUDAYA DAN KETERAMPILAN (SBK) SISWA KELAS III DI UPT SPF SDN KAKATUA KOTA MAKASSAR - Zulvia; Ashari, Meisar; Roslyn (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using collage media on the waste utilization ability of third-grade students in Cultural Arts and Crafts learning. The research was conducted at UPT SPF SDN Kakatua Makassar using a qualitative approach. Data were collected through observation, interviews, and documentation. The research subjects were third-grade students who participated in collage learning activities using plastic waste as the main material. The results of the study indicate that the use of collage media made from plastic waste has an influence on students' ability to utilize waste materials into artistic works. This can be seen from the students’ ability to identify and select plastic waste materials, arrange pieces of materials to form image objects, and produce collage works that vary in terms of shape, color, and composition. In addition, collage activities also increased students’ engagement in the learning process through collaborative work, discussions, and participation in the process of creating artwork. These activities provide concrete learning experiences that help students understand that plastic waste can be reused and transformed into artworks with aesthetic value. Therefore, the use of collage media made from plastic waste can be an effective alternative learning medium in Cultural Arts and Crafts learning at the elementary school level.